The Literary Life and Creativity of Contemporary Writers in the Epistolar Dialogue between A.A. Izmailov and A.A. Tikhonov-Lugovoy - Alexander S. Alexandrov (Studia Litterarum)
The article focuses on the epistolary dialogue between A.A. Izmailov and A.A. Lugovoi, two well-known writers at the beginning of the 20th century. It deals with the most interesting historical and literary facts from the correspondence, e. g. discussion of their works, facts of the literary life of the era, interpretations of the works of brother-writers. Epistolary materials allow to clarify important biographical facts of the two contemporaries. The author examines the method of Izmailov the critic, who, by virtue of his profession, was constantly forced to look for new topics, to think over the structure of more and more new reviews, to incorporate other people’s interpretations prompted in private conversations and personal letters into the texts of his own reviews. The article contains extensive quotations from unpublished letters of two writers.